Implementación de un sistema de contabilidad comercial para el Comercial Luiggy y Hermanas” de la ciudad de Machala, período septiembre-octubre de 2013 - Hualpa Lima, Karina Andrea (2014)
The research work entitled " IMPLEMENTATION OF A SYSTEM OF BUSINESS ACCOUNTING FOR THE " COMMERCIAL LUIGGY AND SISTERS " CITY MACHALA , PERIOD SEPTEMBER- OCTOBER 2013 " was developed in order to organize technical and accounting company , to provide a contribution to economic growth itself, through the effective control of their business; was prepared according to the requirements and regulations of the National University of Loja, for obtaining BA in Accounting and Auditing, Certified Public Auditor. By implementing the commercial accounting system in the aforementioned company , were complied with the objectives as they proceeded to the lifting of the initial inventory which the company did not have a chart of accounts are also created according to business needs and entire accounting process was developed in an orderly and sequential , to finally present the financial statements to be of great importance to the owners and that they will know the real situation of your business and take appropriate and timely decisions. He completed the accounting process will be released to their owners the results , as they are keen to continue the same , since they serve as instructive to improve your internal controls and comply timely with their tax and accounting